Laboratory Study on Hydrate Production Using a Slow, Multistage Depressurization Strategy - Yanlong Li; Chuqiao He; Nengyou Wu; Qiang Chen; Changling Liu; Zhixue Sun; Yurong Jin; Qingguo Meng (Geofluids)
Optimization of the depressurization pathways plays a crucial role in avoiding potential geohazards while increasing hydrate production efficiency. In this study, methane hydrate was formed in a flexible plastic vessel and then gas production processes were conducted at constant confining pressure and constant confining temperature. The CMG-STARS simulator was applied to match the experimental gas production behavior and to derive the hydrate intrinsic dissociation constant. Secondly, fluid production behavior, pressure-temperature (P‐T) responses, and hydrate saturation evolution behaviors under different depressurization pathways were analyzed. The results show that integrated gas-water ratio (IGWR) decreases linearly with the increase in depressurizing magnitude in each step, while it rises logarithmically with the increase in the number of steps. Under the same initial average hydrate saturation and the same total pressure-drop magnitude, a slow and multistage depressurization strategy would help to increase the IGWR and avoid severe temperature drop. The pore pressure rebounds logarithmically once the gas production is suspended, and would decrease to the regular level instantaneously once the shut-in operation is ended. We speculate that the shut-in operation could barely affect the IGWR and formation P‐T response in the long-term level.